Energieeffizienz von Konstantdrucksystemen mit sekundärgeregelten Antrieben beim Einsatz in mobilen Arbeitsmaschinen - Dreher, Thorsten (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2015)
Within this work, it is investigated under which conditions constant pressure systems with secondary controlled drives may be an energetic efficient and cost effective alternative to established mobile hydraulic circuit configurations. For this purpose, a methodology is introduced to evaluate chances and risks at employment of this technology in mobile machines. A demonstrator with three secondary controlled variable displacement drives is developed to confirm the results of the methodology.